β-type silicon nitride powder, resin composition, thermally conductive paste, and method for producing silicon nitride powder

JP7940052B2Active Publication Date: 2026-10-22MARUWA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025038898
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2026-10-22
Estimated Expiration
2045-03-12

Smart Images

  • Figure 0007940052000004
    Figure 0007940052000004
  • Figure 0007940052000005
    Figure 0007940052000005
  • Figure 0007940052000006
    Figure 0007940052000006
Patent Text Reader

Abstract

This invention provides a β-type silicon nitride powder consisting of finer particles while maintaining high fluidity and packing properties. [Solution] The β-type silicon nitride powder is a β-type silicon nitride powder having a β fraction of 80% or more and a specific surface area of ​​5.0 m². 2 It is characterized by having a particle size of 800 nm or less per gram, an average particle diameter of 800 nm or less, and an average aspect ratio of 1.0 to 1.3 for primary particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to β-type silicon nitride powder, resin compositions, thermally conductive pastes, and methods for producing silicon nitride powder. [Background technology]

[0002] In recent years, with the increasing density and power output of electronic devices and semiconductor devices, the heat density of power modules has also increased. Rising temperatures in power modules can cause malfunctions in components and damage to circuit boards. By incorporating β-type silicon nitride powder, an excellent thermally conductive material, as a filler into resin compositions (e.g., substrates, sheets, spacers) and paste-like electronic materials (thermally conductive pastes) such as greases, adhesives, and paints used in such electronic devices and semiconductor devices, heat dissipation performance can be improved.

[0003] Here, there are two types of silicon nitride: α-type silicon nitride (α-Si3N4) and β-type silicon nitride (β-Si3N4), which have different crystalline phases. α-type silicon nitride has the property of irreversibly transforming into β-type silicon nitride at high temperatures (around the sintering temperature of 1500-1700°C). β-type silicon nitride crystal grains are columnar crystal grains elongated in the c-axis direction and are known to have higher thermal conductivity than α-type silicon nitride crystal grains. Therefore, when silicon nitride powder is used as a filler for heat dissipation applications, a higher proportion of β-type silicon nitride crystal grains is considered preferable. On the other hand, the material properties required for fillers include packing ability and fluidity (or kneadability). The higher the packing ability of the filler, the higher the concentration of the powder can be mixed into materials such as resins. Also, the higher the fluidity of the filler, the easier it is to mix the filler with materials at a higher concentration.

[0004] For example, Patent Document 1 discloses a silicon nitride filler that is added to resins and the like that constituting insulating members for the purpose of improving heat dissipation performance. According to Patent Document 1, when the silicon nitride filler contains 50% or more by volume of condensed particles with a particle diameter of 5 μm or more and 200 μm or less, the proportion of particles with a particle diameter of less than 5 μm and particles with a particle diameter of more than 200 μm decreases, thereby improving dispersibility. Furthermore, it is possible to prevent surface roughness and a decrease in mechanical strength of the resin composite obtained by mixing with resins and the like, and to improve thermal conductivity. This silicon nitride filler can preferably be manufactured by a manufacturing method having the following steps. The manufacturing method includes (a) a step of filling a heat-resistant container with silicon, or a mixture of silicon and silicon nitride, (b) a step of producing condensed silicon nitride lumps by a self-combustion reaction in a non-oxidizing atmosphere containing nitrogen at 1 atmosphere or more, and (c) a step of crushing the condensed silicon nitride lumps. The self-combustion reaction of silicon (nitriding combustion reaction) proceeds at high temperatures of 1900°C or higher. During this reaction, silicon nitride particles grow sufficiently, and a condensed mass with an intertwined structure of β-phase silicon nitride particles having well-developed crystalline faces can be obtained as a product. Alternatively, instead of using the self-combustion method to produce silicon nitride filler, a direct nitriding method can be used to nitride silicon powder granules or molded bodies in nitrogen at around 1400°C, further heat treatment at high temperatures to develop β-phase columnar particles, and then the resulting condensed mass can be crushed. The silicon nitride filler thus obtained can be used to make a resin composite containing the silicon nitride filler and a resin composition. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2015-81205 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] In conventional β-type silicon nitride powders such as those described in Patent Document 1, the β-type silicon nitride crystal grains generally consist of elongated columnar particles. However, from the viewpoint of fluidity and filling properties when mixing the filler with resin or paste, it is preferable for the particles to have a shape closer to a sphere and to be smaller in size. On the other hand, a larger particle size of the filler results in a longer heat conduction path, which is advantageous for heat dissipation. Therefore, in order to improve the performance of resin compositions and heat-conducting pastes, the use of sub-fillers with smaller particle sizes to fill the gaps between main fillers, with larger particle sizes as the main filler, has also been considered. The inventors of the present invention aimed to obtain a β-type silicon nitride powder for heat dissipation fillers with even smaller particle sizes that can be used as sub-fillers while maintaining high filling properties and fluidity.

[0007] To solve the above problems, the present invention aims to provide a β-type silicon nitride powder consisting of finer particles while maintaining high fluidity and packing properties, a resin composition containing the β-type silicon nitride powder, a thermally conductive paste containing the β-type silicon nitride powder, and a method for producing the β-type silicon nitride powder. [Means for solving the problem]

[0008] (Composition 1) One embodiment of the present invention is a β-type silicon nitride powder having a β-fraction of 80% or more, Specific surface area is 5.0 m² 2 It is characterized by having a particle size of 800 nm or less per gram, an average particle diameter of 800 nm or less, and an average aspect ratio of 1.0 to 1.3 for primary particles.

[0009] (Configuration 2) A further embodiment of the present invention, the β-type silicon nitride powder, is more preferably characterized in that the β-type silicon nitride powder of configuration 1 contains particles having borehole-shaped depressions.

[0010] (Composition 3) A further embodiment of the present invention is a β-type silicon nitride powder, more preferably a β-type silicon nitride powder having a configuration of 1 or 2, characterized in that it includes particles having a body surrounded by a plurality of rectangular surfaces.

[0011] (Composition 4) A further embodiment of the present invention is a β-type silicon nitride powder, more preferably a β-type silicon nitride powder of any of the three configurations 1 to 3, characterized in that the average circularity of the primary particles is 0.8 or higher.

[0012] (Composition 5) A further embodiment of the present invention is a β-type silicon nitride powder, more preferably a β-type silicon nitride powder of any of the four components, characterized by containing 0.5% by weight or less of Ba.

[0013] (Composition 6) One embodiment of the present invention is a method for producing β-type silicon nitride powder having a β fraction of 80% or more, A process for preparing a mixed powder containing a predetermined amount of SiO2 powder and a predetermined amount of Ba compound powder as raw materials, and a predetermined amount of carbon powder, A step of nitriding the mixed powder by a reduction-nitridation reaction in a nitrogen atmosphere, It is characterized by including.

[0014] (Composition 7) A further embodiment of the present invention is a manufacturing method, more preferably in the method of configuration 7, characterized in that the molar ratio (C / SiO2) of the carbon powder to the SiO2 powder is 2 to 3, and the amount of Ba compound added is 2 to 15 mol% when the SiO2 powder is 100 mol%.

[0015] (Composition 8) A further embodiment of the present invention is a manufacturing method, more preferably in the method of configuration 6 or 7, characterized in that the reduction nitridation reaction is carried out in a temperature environment of 1450 to 1600°C.

[0016] (Composition 9) In a further aspect of the present invention, the production method is more preferably the method according to any one of configurations 6 to 8, wherein the reduction nitridation reaction is carried out in a nitrogen atmosphere at a pressure of 2 atm or higher.

[0017] (Configuration 10) In a further aspect of the present invention, the production method is more preferably the method according to any one of configurations 6 to 9, wherein the Ba compound is a halogen compound.

[0018] (Configuration 11) A resin composition according to one aspect of the present invention is characterized by containing the β-type silicon nitride powder according to any one of configurations 1 to 5.

[0019] (Configuration 12) In a further aspect of the present invention, the resin composition is more preferably the resin composition according to configuration 10, which is a thermoplastic resin or a thermosetting resin.

[0020] (Configuration 13) A thermally conductive paste according to one aspect of the present invention is characterized by containing the β-type silicon nitride powder according to any one of configurations 1 to 5. Effects of the Invention

[0021] The silicon nitride powder of the present invention is, in addition to being a β-type silicon nitride powder, a powder having a specific surface area of 5.0 m 2 / g or less, an average particle diameter of 800 nm or less, and an average aspect ratio of primary particles of 1.0 to 1.3, which has high thermal conductivity as a heat dissipating filler for heat dissipating material applications, improves the fluidity as a filler, and improves the filling property and fluidity into fluids such as molten resins and electronic materials. In addition, the silicon nitride powder of the present invention has an average particle diameter of 800 nm or less, which is smaller than the conventional ones, so that it can be filled as a sub-filler, and can further improve the performance of the resin composition and the thermally conductive paste. Brief Description of the Drawings

[0022] [Figure 1]SEM image of silicon nitride powder from Example 1. [Figure 2] SEM image of silicon nitride powder from Example 2. [Figure 3] SEM image of silicon nitride powder from Example 5. [Figure 4] SEM image of silicon nitride powder of Comparative Example 1. [Figure 5] SEM image of silicon nitride powder in Comparative Example 2. [Figure 6] A schematic diagram illustrating the unique particle shape of the silicon nitride powder of the present invention. [Figure 7] A reference diagram showing how to calculate (a) aspect ratio and (b) circularity of primary particle characteristics. [Modes for carrying out the invention]

[0023] The β-type silicon nitride powder of one embodiment of the present invention is an aggregate of silicon nitride particles, with a β-fraction of 80% or more. That is, the silicon nitride powder contains 80% or more β-type silicon nitride particles, preferably 98% or more, among α-type silicon nitride (α-Si3N4) particles and β-type silicon nitride (β-Si3N4) particles. By containing 80% or more β-type silicon nitride particles, the silicon nitride powder can have significantly higher thermal conductivity compared to α-type silicon nitride powder in which α-type silicon nitride particles are dominant. Furthermore, the β-type silicon nitride powder of the present invention can be used as a heat dissipation (or thermal conductivity) filler to improve heat dissipation by being dispersed in resin compositions (e.g., substrates, sheets, spacers, etc.) or paste-like electronic materials such as greases, adhesives, and paints, although this is not limited to the present invention. The β-type silicon nitride powder of the present invention may be used as a main filler on its own, or, as described later, may be used as a sub-filler for a main filler consisting of relatively large-diameter particles.

[0024] The β-type silicon nitride powder of this embodiment has a specific surface area of ​​5.0 m². 2It is characterized by having a particle size of 2.5 to 5.0 nm or less, and an average particle diameter obtained by converting its specific surface area to 800 nm or less. More specifically, the β-type silicon nitride powder of this embodiment is 2.5 to 5.0 nm 2 It may have a specific surface area of ​​1 / g and an average particle diameter of 300-800 nm. In other words, the β-type silicon nitride powder of this embodiment consists of a fine powder with a relatively small specific surface area and particle diameter compared to conventional β-type silicon nitride powder (see, for example, Comparative Examples 1 and 2), and can exhibit higher fluidity and packing ability when the filler is kneaded with fluids such as resins and pastes. In particular, it can effectively suppress the increase in viscosity when used in thermally conductive pastes.

[0025] Furthermore, the β-type silicon nitride powder of this embodiment is characterized by having an average aspect ratio of 1.0 to 1.3 for its primary particles. The aspect ratio is an indicator of the shape of the primary particles. The average aspect ratio is the average value of the aspect ratios of 50 or more particles. The larger this average aspect ratio, the more particles have a hexagonal prism shape with a larger major axis, which is considered unfavorable for the fluidity of the silicon nitride powder. Figure 7(a) shows a method for calculating the aspect ratio (or needle ratio) of each primary particle in a planar projection image obtained by SEM. As shown in Figure 7(a), the aspect ratio Z is calculated using the following formula, with respect to the absolute maximum length l of the particle and the width w, which is the shortest distance between two straight lines parallel to the absolute maximum length l that enclose the particle. Z=l / w

[0026] The β-type silicon nitride powder of this embodiment has an average aspect ratio of 1.0 to 1.3 for its primary particles, which gives it a shape closer to a perfect sphere compared to the typical elongated columnar particles of β-type silicon nitride crystal grains (see Comparative Example 2). This allows it to exhibit higher fluidity and packing properties when mixed with fluids such as resins and pastes.

[0027] Furthermore, the β-type silicon nitride powder of this embodiment preferably has an average circularity of 0.8 or higher for its primary particles. Circularity is an index indicating the degree of sphericalness of the primary particles. Average circularity is the average value of the circularity of 50 or more particles. The closer the average circularity is to 1, the closer the particles are to spheres, which is considered advantageous for the fluidity of the silicon nitride powder. Figure 7(b) shows a method for calculating the circularity of each primary particle in a planar projection image obtained by SEM. As shown in Figure 7(b), the circularity Y is calculated using the perimeter L and area S by the following formula. Y = 4πS / L 2

[0028] For example, in conventional techniques such as those described in Patent Document 1, when a resin composition is prepared by embedding β-type silicon nitride powder containing many columnar particles in resin, the short axis direction of the columnar particles is oriented in the direction of gravity (thickness direction). This causes anisotropy in thermal conductivity between the thickness direction and the plane direction perpendicular to it in the resin composition. In particular, it is known that β-type silicon nitride crystal grains in conventional silicon nitride powder have a thermal conductivity in the longitudinal direction that is about twice as high as the thermal conductivity in the short axis direction, resulting in the problem that the thermal conductivity in the thickness direction is about half that of the plane direction. The β-type silicon nitride powder of the present invention has an average aspect ratio of 1.0 to 1.3 for its primary particles, so the anisotropy of the thermal conductivity of the particles themselves is smaller than in conventional materials. As a result, the β-type silicon nitride powder of the present invention can also effectively suppress the anisotropy of thermal conductivity between the thickness direction and the plane direction perpendicular to it in the resin composition.

[0029] Furthermore, the β-type silicon nitride powder of this embodiment preferably contains 0.5% by weight or less of Ba. More preferably, the Ba content is 0.05 to 0.5% by weight. In the manufacturing process of the β-type silicon nitride powder of this embodiment, an appropriate amount of Ba compound is used as an additive instead of the conventional Ca compound. Therefore, the β-type silicon nitride powder contains a predetermined amount of Ba.

[0030] Furthermore, SEM images revealed that the silicon nitride powder of this embodiment has a unique particle shape. Figures 1 to 3 are SEM images (magnification 40,000x) of typical examples of silicon nitride powder. On the other hand, Figure 4 illustrates an SEM image (magnification 5,000x) of the silicon nitride powder of Comparative Example 1. Figure 5 illustrates an SEM image (magnification 10,000x) of the silicon nitride powder of Comparative Example 2.

[0031] Observing the SEM images in Figures 1 to 5, it can be seen that the β-type silicon nitride powder of this embodiment was produced through a manufacturing process unique to the present invention, and has a characteristic particle shape compared to the silicon nitride powders of Comparative Examples 1 and 2, which are not produced through such a process. Furthermore, since the silicon nitride powder of the present invention is produced without a grinding process after synthesis, the separation of each particle is good, it has a uniform particle size close to a spherical shape, and the formation of aggregates is significantly suppressed.

[0032] Figure 6 schematically represents the particle shape of a typical β-type silicon nitride crystal grain predominantly observed in SEM images. As shown in Figure 6, since particle 10 is a β-type silicon nitride crystal grain, it is a columnar crystal grain extending in the c-axis direction. This particle 10 has a body portion 11 extending along the c-axis and ends 12 at both ends of the body portion 11 in the c-axis direction. The body portion 11 is formed by multiple rectangular faces that are continuous in the circumferential direction, forming a polygon in a cross-section perpendicular to the c-axis. In other words, the body portion 11 is surrounded by multiple rectangular faces. The ends 12 are convex on both sides of the c-axis. Furthermore, borehole-like recesses 13 are formed at both ends 12. According to the SEM image, these recesses 13 are cylindrical holes or perforated depressions with a pore diameter of approximately 50 to 200 nm. Note that when the particle size is adjusted through a grinding process, a particle shape like the body portion with rectangular faces is not formed.

[0033] In other words, the β-type silicon nitride powder of this embodiment has higher fluidity and, as a heat dissipation filler, possesses improved filling and kneading properties. Furthermore, when the silicon nitride powder of this embodiment is filled, kneaded, and dispersed in a thermoplastic resin or a thermosetting resin, it provides a resin composition with higher heat dissipation performance. For example, a resin composition can be obtained by filling, kneading, and dispersing the maximum filling amount of silicon nitride powder in a molten resin, and then curing the molten resin. Here, the resin composition is not particularly limited, but can be selected from the group consisting of, for example, thermoplastic resins such as polyethylene and polycarbonate, thermosetting resins such as phenolic resins and epoxy resins, silicone resins, rubber, etc. Similarly, when the β-type silicon nitride powder of this embodiment is filled, kneaded, and dispersed in a fluid such as grease, adhesive, or paint, it provides a heat-conductive paste with excellent heat dissipation properties.

[0034] Furthermore, since the β-type silicon nitride powder of this embodiment has an average particle diameter of 800 nm or less, it can also be used as a sub-filler to be dispersed and filled into the gaps between particles of a β-type silicon nitride powder having a larger average particle diameter (for example, greater than 800 nm or greater than 2000 nm) when the main filler is used. That is, the resin composition or thermally conductive paste may contain a first β-type silicon nitride powder having an average particle diameter greater than 800 nm or greater than 2000 nm as the main filler, and a second β-type silicon nitride powder (of this embodiment) having an average particle diameter of 800 nm or less as the sub-filler. As an example, the amount of the first β-type silicon nitride powder (main filler) added is preferably 40 to 65 volume% of the volume of the resin composition or thermally conductive paste, and the amount of the second β-type silicon nitride powder (sub-filler) added is preferably 5 to 30 volume%. For example, a thermally conductive paste containing two types of β-type silicon nitride powder may have a high viscosity of 2-3 Pa·s at 25°C and a high thermal conductivity of 0.5 W / mK or higher.

[0035] Next, a method for producing the β-type silicon nitride powder of this embodiment will be described. The production method of this embodiment includes (1) a step of preparing a mixed powder containing a predetermined amount of SiO2 powder and a predetermined amount of Ba compound powder as raw materials and a predetermined amount of carbon powder, (2) a step of nitriding the mixed powder by a reductive nitridation reaction in a nitrogen atmosphere, and (3) a step of removing the carbon powder from the reductively nitrided mixed powder.

[0036] First, SiO2 powder and Ba compound powder are prepared as raw materials. The SiO2 powder used as the base material preferably contains high-purity fine powder with few metal impurities. The SiO2 powder may also be prepared in the form of a sol (colloidal solution) in which particles are dispersed in a solvent. The Ba compound is preferably BaF2, which is a halogen compound. The raw materials are then prepared so that the amount of Ba compound added is 2 to 15 mol% in molar ratio, with the SiO2 powder being 100 mol%.

[0037] Prepare an appropriate amount of carbon powder. The amount of carbon powder is preferably 2 to 3 times the amount of SiO2 powder in molar ratio (C / SiO2). More preferably, the amount of carbon powder is 2.4 to 2.7 times the amount of SiO2 powder in molar ratio. As the carbon powder, fine particles mainly composed of carbon, such as furnace black or acetylene black, can be used. Furthermore, it is preferable to use carbon with an average particle size of 10 to 50 nm and an ash content of 0.1% or less.

[0038] Next, SiO2 powder, Ba compound powder, and carbon powder are wet-mixed using a planetary mill to prepare a powder slurry. When preparing the slurry, a solution is prepared in which a predetermined amount of dispersant is dissolved in a solvent. Preferably, the solution is an aqueous solution obtained by dissolving a small amount of dispersant in an appropriate amount of pure water. Preferably, the dispersant is a polymeric dispersant selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, and hydroxypropyl cellulose. Preferably, the dispersant is added to the mixture of raw materials and carbon powder in an amount of 0.5 to 1% by weight relative to the raw materials. Wet mixing is performed using a vibratory mill or a planetary mill. After drying the prepared slurry in a constant temperature bath at 120°C, the mixture is passed through a sieve (e.g., with a mesh size of 100 μm) to prepare a mixed powder for synthesis.

[0039] Next, the mixed powder is packed into a carbon sheath of predetermined dimensions. The carbon sheath is placed inside the furnace so that the external atmosphere is introduced into the sheath and the CO gas generated inside the sheath during reductive nitriding is exhausted to the outside.

[0040] Next, the carbon pods filled with the mixed powder are subjected to reductive nitriding treatment in a pressurized nitrogen atmosphere furnace with a carbon heater. The reductive nitriding reaction is preferably carried out at a temperature of 1450 to 1600°C. Furthermore, the reductive nitriding reaction is preferably carried out in a nitrogen atmosphere of 2 atmospheres (0.2 MPa) or higher. The processing time for this reductive nitriding synthesis is preferably 1 to 10 hours. Note that if the furnace pressure during the reductive nitriding treatment is low, SiC is more likely to be generated during the reductive nitriding reaction, so a nitrogen pressure of 2 atmospheres or higher is preferable. Also, if the reductive nitriding treatment temperature is low or the time is short, there is a risk that unreacted SiO2 will remain. On the other hand, if the reductive nitriding temperature is high, the particle growth of silicon nitride particles after reductive nitriding will progress too much, and the columnar shape of the particles will become pronounced, so it is necessary to appropriately adjust the processing temperature and processing time during reductive nitriding.

[0041] The powder after reduction nitriding treatment contains excess carbon powder, so it is heated in dry air at a temperature of 600°C to 700°C to remove the remaining carbon. The heating time varies depending on conditions such as heating temperature, gas flow rate, and powder amount, so it is preferable to adjust it as needed while checking the weight loss. If the heating time is too long, the oxygen content of the silicon nitride powder will increase, so a heating time of about 2 to 12 hours is preferable.

[0042] Through the above steps, the β-type silicon nitride powder of this embodiment can be obtained. The obtained β-type silicon nitride powder can be confirmed by crystal phase analysis by powder X-ray diffraction and SEM image analysis.

[0043] Here, we will explain the mechanism of reductive nitriding. In the reductive nitriding method for silicon nitride powder, it is necessary to mix at least three types of powders: carbon powder, silicon dioxide powder, and additive powder. Conventionally, calcium fluoride (CaF2) or calcium carbonate (CaCO3) have been commonly selected as additives, but the present invention is characterized by the selection of a barium compound (BaF2) as the additive. Generally, additives form a liquid phase during the synthesis of silicon nitride (Si3N4) powder and have the effect of promoting the phase transition from α-Si3N4 to β-Si3N4. The generated liquid phase exists between the silicon nitride particles, and after synthesis, it causes the powders to fuse together. However, additives with high vapor pressure gradually decrease during synthesis and are removed from between the particles after synthesis. Compared to the Ca in conventionally used Ca compounds, the Ba in the Ba compound selected in the present invention has a higher vapor pressure, so the amount that volatilizes during the reductive nitriding reaction is greater than that of Ca, and the effect as an auxiliary agent decreases before the β-type silicon nitride particles grow in the longitudinal direction. On the one hand, if the amount of Ba compound added is too large, the amount of Ba compound remaining during synthesis will be large, causing the β-Si3N4 particles to grow in a columnar shape. On the other hand, if the amount of Ba compound added is too small, the amount of liquid phase generated will be small, resulting in a decrease in the amount of β-Si3N4 produced, and α-Si3N4 will be produced or the particles will fuse together. The manufacturing method of the present invention prevents particle fusion while suppressing particle growth in the longitudinal direction by controlling the amount of Ba compound added as an additive to an appropriate amount, and as a result the specific surface area is 5.0 m². 2 This made it possible to obtain β-type silicon nitride powder with a particle size of less than / g, an average particle diameter of 800 nm or less, and an average aspect ratio of primary particles of 1.0 to 1.3.

[0044] Furthermore, the method for producing β-type silicon nitride powder of the present invention is characterized by not including the pulverization process of silicon nitride aggregates after nitriding, as is done in the conventional method. For example, in the conventional method for producing silicon nitride powder, such as that described in Patent Document 1, silicon nitride aggregates are generated after nitriding, and silicon nitride powder is produced by pulverizing these aggregates. Such pulverization of aggregates increases the amount of coarse aggregates and irregularly shaped particles in the silicon nitride powder, resulting in a significant decrease in the fluidity of the silicon nitride powder. This decrease in the fluidity of the silicon nitride powder increases the viscosity of the fluid into which the silicon nitride powder is mixed, limiting the amount of filler that can be packed into the fluid and its kneadability. Such limitations in packing and / or kneadability hinder the improvement of the heat dissipation performance of the resin composition into which the silicon nitride powder is kneaded. The production method of the present invention, by considering additives, makes it possible to synthesize fine powder with uniform particle size directly without going through a pulverization process after synthesis, and makes it possible to obtain β-type silicon nitride powder with a small particle size and a more spherical shape. [Examples]

[0045] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0046] The β-type silicon nitride powders used in Examples 1-5 and Comparative Examples 1 and 2 were prepared under the following conditions and procedures.

[0047] Pure water containing 0-1.0% by weight of PVP (polyvinylpyrrolidone K30, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) dissolved in the mixed powder was weighed into a resin container. SiO2 powder, an appropriate amount of additive powder (Ba compound or Ca compound), and carbon powder in a molar ratio of approximately 2.4-2.7 times the amount of SiO2 were then added. High-purity SiO2 powder with an average particle size of 0.4 μm was used. A sol in which SiO2 powder (for example, with an average particle size of 0.04 μm) was dispersed in a solvent may also be used. The raw materials were then wet-mixed using the resin container and silicon nitride pebbles. Wet mixing was performed using a vibrating mill or planetary mill to produce a mixed slurry. After drying the mixed slurry in a constant-temperature bath at 120°C, it was passed through a sieve (mesh size 100 μm) to produce a mixed powder for synthesis. The mixed powder was packed into a carbon sheath and placed in a furnace. The carbon sheath was placed inside the furnace with a gap of approximately 10 mm between the frame and the lid, allowing the external atmosphere to enter the sheath. After evacuating the furnace before heating, the nitrogen pressure inside the furnace was increased to 8 MPa, and reductive nitriding was performed at 1450-1600°C for approximately 2-10 hours. Then, the silicon nitride powders of Examples 1-5 and Comparative Examples 1 and 2 were prepared by heating in dry air at a temperature of 600-700°C for 2-12 hours until the weight of the carbon became 0, thereby removing the remaining carbon.

[0048] Powder X-ray diffraction measurements were performed on each of the prepared samples from Examples 1-5 and Comparative Examples 1 and 2. The synthesis of silicon nitride powder was confirmed by referring to the peak positions of the X-ray diffraction patterns. By analyzing the X-ray diffraction patterns, the β fraction, which indicates the mass fraction of β-type silicon nitride in the synthesized powder, was derived. In each sample, the silicon nitride powder showed a β fraction of 98.1-100%, confirming that more than 80% were β-type silicon nitride (β-Si3N4) particles with high thermal conductivity. Furthermore, SEM images (magnification 5000-40000x) were acquired to analyze the particle shape and cross-sectional shape of the silicon nitride powder. The shape characteristics of the primary particles were evaluated by performing image analysis of the obtained SEM images using a computer.

[0049] The various measurements and analyses were performed under the following conditions.

[0050] • Powder X-ray diffraction measurement and analysis Using a Rigaku Corporation Ultima IV powder X-ray diffractometer, the X-ray diffraction intensity of each sample was measured by powder X-ray diffraction using Cu-Kα rays. The integrated intensities of the diffraction patterns of the Si phase, α-type silicon nitride phase, and β-type silicon nitride phase were used to determine the mass fraction of the crystalline phase using the Jovanovic-Kimura method, which is known and expressed by the following three equations.

number

[0051] • Measurement of specific surface area and average particle diameter For each sample of β-type silicon nitride powder, the specific surface area was measured using the BET single-point method, a nitrogen gas adsorption method. The measuring instrument used was a Monosorb, model MS-21, manufactured by Quantachrome. The measured specific surface area Sa (m² / g) was then converted to the average particle diameter D (nm) based on the following formula. Here, ρ is the density of silicon nitride, 3.18 (g / cm³). 3 ) D = 6000 / (Sa × ρ)

[0052] • Observation and analysis of powder shape using SEM The shape of the powder was observed using a scanning electron microscope (JEOL Ltd.) JSM-IT700HR. A silicon nitride powder sample was dispersed on carbon tape using a dry powder disperser (AmbiValue PD-10). A Pt sputter treatment was applied to the powder surface as a conductive coating film, and this was used as the observation sample. The acceleration voltage was set to 5kV, and SE images were acquired at observation magnifications of 5000 to 40000x. The acquired SE images were imported into WinROOF2021 (Ver5.7.4) from Mitani Corporation, and computer-based image analysis was performed. Specifically, the acquired images were processed using filtering, noise reduction, and binarization to enhance the shape characteristics of the primary particles, and the circularity and aspect ratio of the primary particles were measured. The calculation method for the circularity and aspect ratio of the primary particles is described in Figure 7. Particles touching the frame set as the ROI were not used for shape measurement; the shape characteristics of the remaining 50 or more primary particles were measured, and their average values ​​were calculated.

[0053] • Measurement of Ba content The Ba content of the powder was measured using a Rigaku Corporation ZSX PrimusIV scanning X-ray fluorescence analyzer. The sample plate was filled with the powder to be measured, the top surface of the sample plate was covered with a 4 μm ProLene film, and the sample was placed in a container for trace powders. The container was placed in a holder, and elemental analysis was performed using an EZ scan with a φ10 mm sample mask. The weight ratio of Ba content to Si content was calculated from the measurement results.

[0054] Table 1 shows the conditions and various measurement results for each sample in Examples 1-5 and Comparative Examples 1 and 2. Figures 1-3 show SE images of Examples 1, 2, and 5 at an observation magnification of 40,000x, respectively. Figures 4 and 5 show SE images of Comparative Examples 1 and 2 at observation magnifications of 5,000x and 10,000x, respectively.

[0055] [Table 1]

[0056] Examples 1 to 5 and Comparative Example 2 are samples prepared from a mixed powder composed of SiO₂ powder, a Ba compound (BaF₂), and carbon powder. In contrast, Comparative Example 1 is a sample prepared from a mixed powder composed of SiO₂ powder, a Ca compound (CaF₂), and carbon powder. Further, in Examples 1 to 5, the addition amount of the Ba compound (BaF₂) is 2 to 15 mol% when the SiO₂ powder is taken as 100 mol%, whereas in Comparative Example 1, the addition amount of the Ba compound (BaF₂) is 20 mol%.

[0057] When comparing the SEM photographs of Figure 1 to Figure 5, it can be observed that in the obtained SE images of Examples 1, 2 and 5, the separation of each particle is favorable, and the formation of aggregates is significantly suppressed. In addition, Examples 1, 2 and 5 have a unique particle shape as shown in Figure 6, compared with Comparative Examples 1 and 2. Further, Examples 1, 2 and 5 exhibit a smaller aspect ratio and a more nearly spherical particle shape than Comparative Examples 1 and 2.

[0058] Table 1 quantitatively shows the characteristics of each sample.

[0059] According to Table 1, Examples 1 to 5 show 2.5 to 4.8 m 2 specific surface area Sa of / g, and an average particle diameter D of 392 to 749 nm. In contrast, Comparative Example 1 using a Ca compound as an additive shows a specific surface area Sa of 0.9 m 2 / g, and an average particle diameter D of 2028 nm. That is, in Examples 1 to 5, the particle diameter is significantly smaller than that of the conventional β-type silicon nitride powder produced using a Ca compound. On the other hand, Comparative Example 2 in which the amount of the Ba compound as an additive is increased shows 2.1 m 2The specific surface area Sa per g and the average particle diameter D of 897 nm are shown. It is thought that the increase in the Ba compound led to increased crystal growth, resulting in an average particle diameter exceeding 800 nm compared to Examples 1-5. The Ba content of the silicon nitride powder in Examples 1-5 was 0.05-0.46%, while the Ba content of the silicon nitride powder in Comparative Example 2 was 0.67% (Comparative Example 1 used a Ca compound, so the Ba content of the silicon nitride powder was 0.00%).

[0060] Furthermore, according to Table 1, Examples 1 to 5 showed an average aspect ratio of 1.1 (i.e., within the range of 1.0 to 1.3) and an average circularity of 0.82 to 0.90 in primary particle characteristics. In contrast, Comparative Example 1, which used a Ca compound as an additive, showed an average aspect ratio of 1.2 and an average circularity of 0.86, showing no significant difference. On the other hand, Comparative Example 2, in which the amount of the Ba compound additive was increased, showed an average aspect ratio of 3.1 and an average circularity of 0.55. In other words, in Comparative Example 2, by increasing the amount of Ba compound added from 15% to 20%, the columnarization of the particles progressed excessively, resulting in the formation of elongated columnar particles that are undesirable as fillers.

[0061] Furthermore, thermally conductive pastes were prepared by filling them with the two types of β-type silicon nitride powder samples (see Table 1) prepared and evaluated as described above, as the main filler and sub-filler, and their viscosity and thermal conductivity at 25°C were evaluated. The thermally conductive pastes for Examples 6-8 and Comparative Examples 3 and 4 were prepared under the following conditions and procedures.

[0062] A main filler (first silicon nitride powder) and a subfiller (second silicon nitride powder) were mixed in predetermined proportions. A sample of thermally conductive paste (silicone paste) was prepared by adding the silicon nitride filler to a silicone oil (KF-96-30CS) with a kinematic viscosity of 30 cSt at 25°C, so that it made up 65 vol% of the total, and then vacuum mixing using a rotary mixer.

[0063] The various measurements were performed under the following conditions.

[0064] • Measurement of viscosity (at 25°C) The viscosity of a thermally conductive paste at 25°C was measured using a cone-plate viscometer (TV-100E, 1°34'×R24 cone rotor) manufactured by Toki Sangyo Co., Ltd.

[0065] • Measurement of thermal conductivity The thermal conductivity of the paste was measured using a thermal conductivity measuring device (TRIDENT, C-Therm Technologies Ltd.). Specifically, 1.8 ml of thermally conductive paste was placed in a Modified Transient Plane Source sensor, and five measurements were taken for each sample. The average value was used as the measured value.

[0066] Table 2 quantitatively shows the viscosity and thermal conductivity of each sample.

[0067] [Table 2]

[0068] According to Table 2, the thermally conductive pastes of Examples 6 to 8 used the β-type silicon nitride powder of Comparative Example 1, which has a relatively large particle size (approximately 2000 nm), as the main filler, and the β-type silicon nitride powder of Examples 1, 2, and 5, which has a relatively small particle size (approximately 800 nm or less), as the subfiller. On the other hand, Comparative Example 3 used the β-type silicon nitride powder of Comparative Example 1, which has a relatively large particle size (approximately 2000 nm), as the main filler without using a subfiller. Comparative Example 4 used the β-type silicon nitride powder of Comparative Example 1, which has a relatively large particle size (approximately 2000 nm), as the main filler, and the β-type silicon nitride powder of Comparative Example 2 as the subfiller.

[0069] As shown in Table 2, Examples 6-8 exhibited a viscosity of 2.2-3.0 Pa·s and a thermal conductivity of 0.54-0.57 W / mK. In contrast, Comparative Example 3, which did not contain a subfiller, exhibited a viscosity of 2.9 Pa·s and a thermal conductivity of 0.45 W / mK, indicating that Examples 6-8 showed higher thermal conductivity than Comparative Example 3. Comparative Example 4 exhibited a viscosity of 6.7 Pa·s and a thermal conductivity of 0.46 W / mK. In other words, even when the β-type silicon nitride powder of Comparative Example 2, which has a relatively small average particle diameter (897 nm), was added as a subfiller, an increase in viscosity was observed compared to Comparative Example 3 due to its needle-like particle shape, and furthermore, no improvement in thermal conductivity was observed. That is, it has been demonstrated that the β-type silicon nitride powder of the present invention, when added as a subfiller, can effectively improve the thermal conductivity (by at least 30%) while keeping the viscosity of the thermally conductive paste low.

[0070] The present invention is not limited to the embodiments described above, and can be implemented in various forms as long as they fall within the technical scope of the present invention. [Explanation of Symbols]

[0071] 10 particles 11 Torso 12 End 13 recess

Claims

1. A β-type silicon nitride powder having a β-fraction of 80% or more, Specific surface area is 5.0 m² 2 A β-type silicon nitride powder characterized by having a concentration of less than or equal to / g, an average particle diameter of 800 nm or less, an average aspect ratio of primary particles of 1.0 to 1.3, and containing 0.5% by weight or less of Ba.

2. The silicon nitride powder according to claim 1, characterized in that it contains particles having borehole-shaped depressions.

3. The β-type silicon nitride powder according to claim 2, characterized in that it contains particles having a body surrounded by multiple rectangular surfaces.

4. The β-type silicon nitride powder according to claim 1, characterized in that the average circularity of the primary particles is 0.8 or higher.

5. The β-type silicon nitride powder according to Claim 1, characterized in that it contains 0.05 to 0.5% by weight of Ba.

6. A method for producing β-type silicon nitride powder having a β fraction of 80% or more, A predetermined amount of SiO 2 A process for producing a mixed powder containing a raw material containing powder and a predetermined amount of Ba compound, and a predetermined amount of carbon powder, A step of nitriding the mixed powder by a reduction-nitridation reaction in a nitrogen atmosphere, Includes, A method characterized in that the mol ratio (C / SiO2) of the carbon powder to the SiO2 powder is 2 to 3, and the amount of Ba compound added is 2 to 15 mol% when the SiO2 powder is 100 mol%.

7. The method according to 6, characterized in that the reduction nitridation reaction is carried out in a temperature environment of 1450 to 1600°C.

8. The method according to 6, characterized in that the reduction nitridation reaction is carried out in a nitrogen atmosphere of 2 atmospheres or more.

9. The method according to 6, characterized in that the Ba compound is a halogen compound.

10. A resin composition characterized by containing the β-type silicon nitride powder described in any one of claims 1 to 5.

11. The resin composition according to claim 10, characterized in that it is a thermoplastic resin or a thermosetting resin.

12. A thermally conductive paste characterized by containing the β-type silicon nitride powder described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Silicon nitride-based powder and its manufacturing method, silicon nitride-based sintered compact and its manufacturing method, and circuit board

    JP2002097005A

  • Silicon nitride filler, resin composite, insulating substrate, and semiconductor sealant

    JP2015081205A

  • Method of producing high purity silicon nitride powder

    JP2020023406A

  • Method for producing silicon nitride

    JP2021113138A

  • Silicon nitride powder for sintering

    JP2024010444A